TINJAUAN YURIDIS PENGHINAAN TERHADAP PENGADILAN DALAM SISTEM PERADILAN PIDANA INDONESIA - Wildan Syafitri; Erdianto '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The criminal justice system is responsible for the judicial system to gain the trust of the public and the respect of society both nationally and internationally. In fact, the performance of law and law enforcement is still considered less meeting the expectations and feelings of justice. As a result, the respect and trust towards this institution was virtually no longer so admirable behavior still common and cause harassment to the court (Contempt of Court). The purpose of this is skripisi; The first to know the contempt of court in the Indonesian criminal justice system. Second, to find out the policy of criminalization contempt of court in the Indonesian criminal justice system.This type of research can be classified into types of normative legal research, research that discusses the basics of law, the legal system, the legal status of the synchronization, in this case the author discusses the general principles of law. This research was done by researching library materials or secondary data such as legislation and books written by lawyers associated with the title of the research, articles, journals and various other sources. Source of data used is secondary data sources. Secondary data were divided into three types: primary legal materials, secondary law and tertiary legal materials, data collection techniques used in this research method literature review. From the research, there are two main problems that can be inferred. First, Contempt of court (Contempt of Court) is one of the many problems affecting society for that reason the severity of claims to establish the rule of Contempt of Court systematically and individually. Second, as for the criminalization of policy constraints in Contempt of Court (Contempt of Court) is on a different system between the State of Indonesia as a follower of Civil Law, with its criminal justice system non adversary system, while in the State which adopts the Common Law system adheres adversary. Suggestions Author, First, should be made a rule that governs the actions of contempt of court (Contempt of Court) in a separate law, to be able to benchmark what should be categorized as an act of contempt of court (Contempt of Court) because during this become an obstacle for law enforcement officers in dealing with contempt of court action (contempt of court). Second, should the public as justice seekers must have a sense of justice, must heed the order in the conference to realize peace and order and expedite the trial process and hoped to law enforcement officials to be professional in their duties in order to gain certainty, justice and expediency as a theory legal purposes.Keywords: Contempt - Court - Criminal Justice System